Arthroscopic Reduction and Internal Fixation of a Rim Fracture - Torres-Eguía, Raul (Arthrosc Tech, 2017)
Femoroacetabular impingement is uncommonly associated to a rim fracture. Complete resection of the fragment might result in iatrogenic instability or poor femoral head coverage. In this report, we describe the step-by-step surgical technique of arthroscopic partial resection of a rim fracture, reduction and internal fixation of the remaining fragment to correct the impingement, and preserve the adequate acetabular coverage.